Prevalence of mutations responsible for glycogen storage disease type-II and congenital myasthenic syndrome in Brazilian Brahman cattle - Trecenti, Anelize S. [UNESP]; Fernandes, André V. [UNESP]; Andrade, Danilo G.A. [UNESP]; Pimenta-Oliveira, Andreza [UNESP]; Borges, Alexandre S. [UNESP]; Oliveira-Filho, José P. [UNESP] (FapUNIFESP (SciELO), 2018)
Glycogen storage disease type II (GSD-II) and congenital myasthenic syndrome (CMS) are important autosomal recessive disorders in Brahman cattle. The objective of this study was to investigate the presence of mutations responsible for GSD II (E7, c.1057-1058delTA; and E13, c.1783C>T) and CMS (c.470del20) in purebred Brazilian Brahman cattle and in purebred Brahman bulls that were routinely used in breeding programs in Brazil. A total of 276 purebred Brahman cattle (167 females and 109 males, with ages ranging from 12-24 months) and 35 frozen semen samples taken from purebred Brahman bulls (22 bulls from the USA, 11 Brazilian bulls, one Argentine bull and one Australian bull) were used in this study. Genomic DNA was purified from hair root samples and from semen samples. Purified DNA was used in PCR genotyping to mutations c.1057-1058delTA (E7) and c.1783C>T (E13) in the GAA gene and c.470del20 in the CHRNE gene. The PCR products were purified and sequenced. The genotypic frequencies per polymorphism were estimated separately. Of the 276 Brahman cattle tested, 7.3% were identified as heterozygous for E7. All Brahman cattle studied were homozygous for the wild-type E13 allele. The E7 mutations was identified as heterozygous in 8.6% (3/35) of the commercial semen samples, whereas the E13 mutations was not identified. The c.470del20 mutation was identified as heterozygous in 0.73% of the hair root samples, but this mutation was not present in any semen sample assessed. No study had previously evaluated the prevalence of mutations responsible for GSD II or CMS in Brazilian Brahman cattle. In summary, the E7 and c.470del20 mutations are present in the Brazilian Brahman herd, and control measures should be adopted to prevent an increase in the incidence of GSD-II and CMS in Brahman cattle in Brazil.
Keywords: Brazil; Brazilian Brahman cattle; congenital myasthenic syndrome; generalised glycogenosis; glycogen storage disease; Mutation; Pompe disease